1984
DOI: 10.1117/12.941776
|View full text |Cite
|
Sign up to set email alerts
|

Optical Performance And Process Characterizations Of Several High Contrast Metal-Ion-Free Developer Processes

Abstract: Projection print quality is dependent upon the response of the resist /developer system to the optically projected image.For this reason, it is critical, during process optimization, to relate final pattern quality to both the chemical and physical contrast terms. One method for doing this is to monitor resist /developer response in the absence and then the presence of diffracted light.These results are then compared to the predicted optical requirements.For best performance, the resist /developer (or chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Figure 3 shows with simulation using PROLITH™ 3D v7.2.2 (KLA-Tencor/FINLE Div. ), how the isofocal region 14,15 shifts with base diffusivity for 90nm lines for pitches of 180nm and 540nm. In these simulations it is observed that the isofocal region for the 540nm pitch moves from 72nm to 84nm, while it moves 8nm, from 86nm to 94nm for the 180nm pitch with most of its shift occurring once the base's diffusivity exceeds that of the resist's acid.…”
Section: Opc With Base Diffusivity (And Other Resist Characteristics)mentioning
confidence: 99%
“…Figure 3 shows with simulation using PROLITH™ 3D v7.2.2 (KLA-Tencor/FINLE Div. ), how the isofocal region 14,15 shifts with base diffusivity for 90nm lines for pitches of 180nm and 540nm. In these simulations it is observed that the isofocal region for the 540nm pitch moves from 72nm to 84nm, while it moves 8nm, from 86nm to 94nm for the 180nm pitch with most of its shift occurring once the base's diffusivity exceeds that of the resist's acid.…”
Section: Opc With Base Diffusivity (And Other Resist Characteristics)mentioning
confidence: 99%